Applied machine learning for healthcare and life sciences using AWS : transformational AI implementations for biotech, clinical, and healthcare organizations - Ratan, Ujjwal (Packt, 2022)
"This book is specifically tailored toward technology decision-makers, data scientists, machine learning engineers, and anyone who works in the data engineering role in healthcare and life sciences organizations. Whether you want to apply machine learning to overcome common challenges in the healthcare and life science industry or are looking to understand the broader industry AI trends and landscape, this book is for you. This book is filled with hands-on examples for you to try as you learn about new AWS AI concepts."--Provided by publisher